The Internet [Technology 2000 analysis and forecast]. - Comerford, R.
In developed nations around the world in 1999, the Internet entered the mainstream of consciousness. In 2000, it enters the mainstream of daily life. Improvements in speed, accessibility, and usefulness-coupled with the lowest prices ever for computers and free Internet access, or vice versa-will likely make for the most explosive growth yet. Business is expecting to make the most of that growth. The only obstacle to global progress is regulation and the need to make the Internet robust enough to stand the traffic. The forecasts include raising the speed limit of the information highway, Internet name registration goes global, the US lifts constraints on encryption exports, and the ranks of the digital economy get crowded
Keywords: Internet; Internet name registration; Internet robustness; Digital economy; Encryption exports; Free Internet access; Information highway; Regulation; Technology forecast